Analysis the Effect of the Moon Phase in Optimization of Growth and Survival Mangrove Crabs (Scylla olivacea) in Silvofishery Systems (Torani Journal of Fisheries and Marine Science, 2024)
Silvofishery is a cultivation activity in mangrove or mangrove areas, the type of biota that can be cultivated in mangrove areas using a silvofishery system, one of which is mangrove crab (Scylla olivacea). The research was carried out in the mangrove area of ​​Mandalle Village, Mandalle District, Pangkajene and Islands Regency, South Sulawesi Province. The test animal used was a male mangrove crab (S. olivacea) weighing 146–168 g which was kept in a circular bamboo cage with a diameter of 2.25 m. The results of the Kruskal Wallis analysis show that the moon phase has a significant effect on the absolute growth and daily growth rate of mud crabs, the dark moon phase produces the highest average absolute growth of 14.53 g with a daily growth rate of 0.57%/day. Meanwhile, the full moon phase produced the lowest average absolute growth of 7.82 g with a daily growth rate of 0.32%/day. The results of the Kruskal Wallis analysis showed that differences in lunar phases had no significant effect on the survival of mud crabs.